Making sustainable commitments : an environment strategy for the World Bank - World Bank. (Washington, D.C. : World Bank, 2001)
This Environment Strategy outlines how the World Bank works with client countries to address their environmental challenges as well as to ensure that World Bank projects and programs integrate principles of environmental sustainability
Includes bibliographical references: p. 221-234.
ne 28/01/2019
Ref
Keywords: Sustainable development; Economic development